How to eat fried worms - Rockwell, Thomas, 1933-; McCully, Emily Arnold (New York : Yearling, 2006)
A small boy is challenged by a friend to eat fifteen worms in fifteen days for fifty dollars.
Originally published: New York : F. Watts, 1973.
"A Yearling book."
Keywords: Worms -- Fiction; Contests -- Fiction